Talent Pool on The Appointment of Directors of PLN (Persero) Viewed from Good Corporate Governance - Ikhwan Nul Yusuf Maulana; Elisatris Gultom; Sudaryat Sudaryat (Unnes Law Journal, 2020)
Talent Pool on the appointment of BUMN Directors that has been implemented at this time still leaves problems. This research aims to know how the application of the Talent Pool on the appointment of Directors of PLN (Persero) viewed from Good Corporate Governance and the implications for compliance and performance aspects. The research method used in this study is a normative juridical approach which is done analytically descriptive. The results showed there were still mismatches in the application of the Talent Pool on the appointment of the Directors of PLN (Persero) to several GCG principles that are transparency principle related to the need for an information system to appoint Directors of BUMN which is transparent and accountable, accountability principle is relating to the need for the development of a performance appraisal system for Directors, BoC and Shareholders and the accountability arrangements for professional institutions or teams formed by the Minister of BUMN in conducting due diligence and propriety tests for candidates for the BoD and independence principle is relating to the process of appointing BUMN Directors which must be done in stages by involving the final assessment by Tim Penilai Akhir. The implications of the application of the Talent Pool that applies GCG principles have a significant impact on compliance and performance aspects, this is evidenced by increased compliance with applicable laws and regulations through prevention of acts against the law and increased performance through company profitability.